2017
DOI: 10.21010/ajtcam.v14i4.10
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis Induction of Epifriedelinol on Human Cervical Cancer Cell Line

Abstract: Background: Present investigation evaluates the antitumor activity of epifriedelinol for the management of cervical cancer by inducing process of apoptosis. Methods: Human Cervical Cancer Cell Line, C33A and HeLa were selected for study and treated with epifriedelinol at a concentration of (50-1000 µg/ml). Cytotoxicity of epifriedelinol was estimated by MTT assay and induction of apoptosis was assessed by estimating the activity of caspase 3, 8 and 9 enzyme, apoptosis assay and translocation of cytochrome c. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“… NCU0041 0.032 0.032 Red Guava ( Psidium guajava L . ) Mugwavha T E (Central and South America) C/W HG I Domestic utensils, food, drink, medicine a) Fruits: beverage; jelly; b) Leaves: stop bleeding wounds; c) Stem: brooms 1 a) Fruit: food; b) Whole plant: shade tree; c) Roots, leaves, bark: wounds; venereal disease [ 9 , 14 , 15 ]. NCU0117, 135, 32, 66, 110, 149, 167 0.129 0.161 Ochnaceae Yellow-peeling tree ( Brackenridgea zanguebarica Oliv) Mutavhatsindi T N W F/W Medicine a) Roots, stem, bark and leaves: medicine to protect homesteads and territories from enemies; b) Bark: Added to other medicines to enhance its potency 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… NCU0041 0.032 0.032 Red Guava ( Psidium guajava L . ) Mugwavha T E (Central and South America) C/W HG I Domestic utensils, food, drink, medicine a) Fruits: beverage; jelly; b) Leaves: stop bleeding wounds; c) Stem: brooms 1 a) Fruit: food; b) Whole plant: shade tree; c) Roots, leaves, bark: wounds; venereal disease [ 9 , 14 , 15 ]. NCU0117, 135, 32, 66, 110, 149, 167 0.129 0.161 Ochnaceae Yellow-peeling tree ( Brackenridgea zanguebarica Oliv) Mutavhatsindi T N W F/W Medicine a) Roots, stem, bark and leaves: medicine to protect homesteads and territories from enemies; b) Bark: Added to other medicines to enhance its potency 1 .…”
Section: Resultsmentioning
confidence: 99%
“… NCU0038, 61, 86 0.161 0.097 Solanaceae Black or Common Nightshade ( Solanum nigrum L) Muxe H E (Europe) W HG Food a) Leaves: cooked and eaten with porridge and other vegetables. a) Leaves: cooked and eaten with porridge; with meat or other vegetables; malaria and dysentery; anal are a known analgesic effects on toothache; b) used as a cholagogue; c) Roots and leaves: wounds [ 6 , 7 , 15 ]. NCU0108 0.032 0.032 Ulmaceae White Stinkwood ( Celtis africana Burm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The result showed that emodin was related to induction of cell cytotoxicity, apoptosis, oxidative stress, and DNA damage. When HeLa cells were treated by epifriedelinol isolated from Aster tataricus and Vitex peduncularis, the level of caspase-3, -8, and -9 were increased and Bcl-2, -xL, survivin, and actin were decreased at doses of 50 µg/mL, 100 µg/mL, 250 µg/mL, 500 µg/mL, and 1000 µg/mL for 72 h [30]. Through the mechanisms, it reduced cell viability and induced apoptosis by downregulating the expression of anti-apoptotic protein and enhancing the expressions of pro-apoptotic protein.…”
Section: Compoundsmentioning
confidence: 99%